Trusted Digital Repositories for Document Preservation: A Tools’ Evaluation - Oliveira, Ana; Moura, Luís; Terra, Ana Lúcia (Bobcatsss, 2023)
Grounded in a review of the preservation concept in trusted digital repositories, this paper aims to address how different trusted digital repositories operate while in the process of preserving digital objects. For this purpose, a literature review and an evaluation of trusted digital repositories’ tools were carried out. A research was first conducted on several concepts related to this topic, namely digital preservation and its policies, reliable digital repositories and their rules. A search on theoretical background and a survey of available trusted digital repositories were performed. A set of tools was identified and then evaluated, and for that purpose several steps were outlined. First, in the criterion identification phase, the several criteria that a reliable digital repository must meet were identified, and then classified as mandatory or complementary. Then, functionalities of different software were highlighted and a comparison was made between them, resulting in a comparative table that led to the choice of DSpace software. This software is the most complete tool, and accomplishes the most important functionalities of a trusted digital repository. Furthermore, it is one of the most used software worldwide for trusted digital repositories, which grants it a high level of reliability.